2013
DOI: 10.1002/cm.21153
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of inhibition of endothelial cell migration by taxanes

Abstract: Several antiangiogenic mechanisms have been proposed for the widely-used cancer chemotherapeutic drugs taxotere (docetaxel) and taxol (paclitaxel), but none has been definitively identified. We analyzed their effects at a range of concentrations on migration and mitosis of human umbilical vein endothelial cells (HUVECs) on microtubule and focal adhesion morphology and microtubule dynamic instability during migration. Both taxanes inhibited migration by inhibiting both maintenance of the forward direction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Identified compounds (Kamath et al, 2014). However, despite the effect on actin, and actin's involment in cell migration (Yamaguchi and Condeelis, 2007), there was no significant effect on cell migration by any of the E. foeminea extracts or fruit juice.…”
Section: Fractionmentioning
confidence: 99%
“…Identified compounds (Kamath et al, 2014). However, despite the effect on actin, and actin's involment in cell migration (Yamaguchi and Condeelis, 2007), there was no significant effect on cell migration by any of the E. foeminea extracts or fruit juice.…”
Section: Fractionmentioning
confidence: 99%
“…Drug binding and suppression of microtubule dynamic instability also impair many interphase functions of microtubules including migration, intracellular trafficking, and cell secretion [11][12][13]. Several studies have briefly reported some of ixabepilone's properties in cells [14,15] and in vitro [7][8][9], but there has been no full elucidation of its mechanism of action including its response to altered tubulin isotype expression.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubules are dynamic tube shaped protein polymers (25 nm in diameter) that play important roles in determining cell shape, polarity, cellular migration, signaling, and mitosis [31]–[33]. Microtubules can undergo two unusual non-equilibrium dynamic behaviors, dynamic instability, the switching between growth and shortening at microtubule plus ends [34], [35], and treadmilling, the net plus end assembly and minus end disassembly (reviewed in [31]).…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule dynamics are rapid during mitosis and are critical for the accurate and time-sensitive attachment of chromosomes to the mitotic spindle, movement of the chromosomes to form the metaphase plate, and production of proper tension at the kinetochores, all of which are essential for the passage through the metaphase/anaphase spindle checkpoint [36], [37]. Microtubule dynamics are also important in cell polarity, cell migration and metastasis [33].…”
Section: Introductionmentioning
confidence: 99%